Species and Cell Types Difference in Tryptophan Metabolism. (January 2013) - Murakami, Yuki; Saito, Kuniaki
L-Tryptophan (L-TRP) is a nutritionally essential amino acid and the kynurenine (KYN) pathway is the major route of L-TRP catabolism. Besides being synthesized for proteins, L-TRP and its metabolites have critical roles for the functions of nervous and immune systems. Many researches show that optimal amounts of L-TRP in diets depend on species, developmental stages, environmental factors and health status. We have shown that KYN pathway-related enzyme activities vary among species, tissue and cell types in physiological conditions. Furthermore, the response of these enzyme activities to systemic and/or central nervous system immune activation and inflammation depends on species and cell types. Thus, it is very important to choose appropriate animal species and cell types in which to evaluate the physiologic and pathologic effects of increased KYN pathway metabolism. We believe that understanding L-TRP metabolism among species and cell types provides a better idea for analysis of human pathological condition.